Absolute SPECT/CT quantification of cerebral uptake of 99mTc-HMPAO for patients with neurocognitive disorders - Welz, Friedrich; Sanders, James C.; Kuwert, Torsten; Maler, Juan; Kornhuber, Johannes; Ritt, Philipp (Nuklearmedizin - NuclearMedicine, 2016)
It was reported from planar imaging studies that the cerebral uptake of injected 99mTc-HMPAO activity is about 4–7% in humans. Recent work has shown that modern SPECT/ CT devices are able to quantify the tissue concentration of radioactivity in vivo in absolute units (Bq/ml), while avoiding the limitations of planar techniques. The aims of this study were (a) to determine the cerebral uptake of 99mTc-HMPAO in absolute units in SPECT/CT, (b) to investigate potential differences in absolute tracer uptake for patients suspected of dementia. Patients, methods: We performed 99mTc-HMPAO SPECT/CT in 65 patients with suspected dementia. 99mTc-HMPAO uptake was determined using a previously published quantitative SPECT/CT protocol. The absolute HMPAO uptake and the results of a regionalized analysis were compared for MMSE and NINCDS-ADRDA based patient groups. Results: The mean absolute uptake of 99mTc-HMPAO for our patient population was 4.3 ± 0.8% of the injected dose. The uptake, as well as the regionalized analysis yielded significantly different results for low ( 23) and high (>23) MMSE groups and also for some of the NINCDS-ADRDA groups. Conclusion: Our results show that the absolute cerebral uptake of 99mTc-HMPAO is in the range of previously reported results, obtained by planar techniques. Absolute uptake is significantly different between the patient groups.
Keywords: Absolute quantification; SPECT/CT; HMPAO; brain perfusion